Kepastian Hukum Akun Youtube Sebagai Objek Warisan dalam Perspektif Hukum Perdata Indonesia - Rayi Kharisma Rajib; Nur Hasna Maulida; Christina Tri Novita Marpaung (CV. KAMPUS AKADEMIK PUBLISING, 2026)
With the advancement of digital technology, digital assets with economic value have emerged, including YouTube accounts that generate income. This raises legal questions within the context of Indonesian inheritance law, as Indonesian inheritance law still focuses on tangible property based on the Civil Code (KUHPerdata). The objective of this study is to analyze the status of YouTube accounts as digital assets, as well as their legal certainty as objects of inheritance. The method employed is a normative legal approach, based on an analysis of statutory texts and a literature review. The results of this study indicate that YouTube accounts can be classified as intangible assets, as they possess economic value and are manageable. From a legal perspective, based on Articles 830 and 833 of the Civil Code, a YouTube account can be part of an estate. However, due to the lack of clear regulations and challenges arising from contractual relationships with digital platforms, legal certainty remains low. Therefore, regulatory updates are needed to ensure legal certainty regarding the inheritance of digital assets.